How do you write an equation in slope-intercept form for(-2,1); m=1

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

How do you write an equation in slope-intercept form for(-2,1); m=1

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

Plug it into the equation: (y-y1) = m (x-x1) as (-2,1) = (x1,y1) and m = 1
you're just getting people to do your homework, this question is the exact same as the last one you asked. You know these people won't be here when it comes test time
Can you solve that for me Mira? I can guide you through.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

okay so, 1= 1(-2) +b right?
(y- 1) = 1 (x- (-2) y - 1 = 1 (x + 2) y - 1 = 1x + 2 y = 1x +1
wait what D: I'm so confused.
Haha, okay lets take it step by step.
The equation we plug these in is: (y -y1) = m (x-x1) The given points are: (-2, 1) which substitutes as (x1,y1) If we put it all together, we get: (y - 1) = m (x - (-2) Understood?
Yes okay..
equation is y=mx+b << u have (-2,1), which is x=-2, y=1, and m=1.... plug back in--- 1=1(-2)+b, solve for b, u get b=3, then rewrite, y=1x+3
Now lets plug in for m as well, giving us: (y - 1) = 1 (x - (-2)
(y- 1) = 1 (x + 2) is what it becomes when simplified.
yeah so 1=1x-2?
im not following ur way, katrina..... u lost me lol
First: You forgot about the "y" before 1 = 1x - 2
Second: Its y - 1 = 1x + 2 (1x PLUS 2)
(y- 1) = 1 (x- (-2) y - 1 = 1 (x + 2) y - 1 = 1x + 2 <<
Lol Yep.
got cha, i think the equation y=mx+b is way easier to remember
Hmm, but you have to begin with : (y-y1) = m (x-x1)
OH I UNDERSTAND THANK YOU!!!!!!

Not the answer you are looking for?

Search for more explanations.

Ask your own question